(untitled) (International journal of artificial intelligence, 2024)
Currently, phraseology in the media is mobile: it does not stand still and is constantly evolving. The globalization of all vital spheres of society has also affected the sphere of language, thereby contributing to the emergence of new phraseological units in mass media texts. These units come there from all spheres of human activity, reflecting the picture of modern society, which contributes to the emergence of scientific interest in the study of the sources in which the process of formation of these units took place, and the ways, the so-called information guides, which provoke their appearance in the media.